Beam Projection Effect in the Radiographic Evaluation of Ankle Valgus Deformity Associated With Fibular Shortening. Issue 8 (December 2016) - Jang, Woo Young; Park, Moon Seok; Yoo, Won Joon; Chung, Chin Youb; Choi, In Ho; Cho, Tae-Joon
Abstract : Background: Fibular shortening is one of the most common causes of ankle valgus deformity in children, and is frequently observed in patients with hereditary multiple exostoses (HME). It has been observed that the lateral distal tibial angle (LDTA) measured on the teleoradiograph differs from that on the ankle anteroposterior (AP) radiograph. The effect of the beam projection angle in the measurement of ankle valgus deformity associated with fibular shortening in HME patients was investigated. Methods: Fourteen ankles showing valgus deformity associated with fibular shortening from 14 HME patients comprised the short fibula group. Nineteen ankles with normal ankle alignment from 19 patients comprised the control group. The LDTA on the AP radiograph, teleoradiograph, and 3 coronal planes of 3-dimensional computed tomographic scans were measured and compared. Results: In the short fibula group, the LDTA measured on the ankle AP radiograph was significantly larger than that on the teleoradiograph (79.6±4.3 vs. 75.0±6.2 degrees, P =0.001), whereas there was no significant difference in the control group ( P =0.36). In the short fibula group, the LDTAs measured on the 3 coronal planes of 3-dimensional computed tomography showed that the ankle valgus measurement significantly increased from anterior to posterior planes ( P =0.001), whereas there was no significant difference in the control group ( P =0.85). Conclusions: Measurement of ankle valgus deformity depends on the direction of beam projection and ankle valgus deformity is more severe in the posterior coronal plane of the ankle joint. This discrepancy should be taken into consideration in the planning of ankle valgus deformity management. Level of Evidence: Level IV—diagnostic.